Cytoplasmic granules in bovine oocytes do not affect embryonic or fetal development - Rosa, Paola Maria da Silva [UNESP] (2024)
Oocyte cytoplasmic evaluation is based on homogeneity and granular appearance. Our study investigated if a granular cytoplasm, highly heterogeneous, would affect oocyte competence in bovine. In two experiments, bovine cumulus-oocyte complexes (COCs) with homogeneous cytoplasm (control, CC) and granulated cytoplasm (granular, GC) were selected from a regular pool of COCs. Experiment 1 was performed with slaughterhouse ovaries, and Experiment 2 was carried out in Girolando COCs obtained from ovum pick-up. Granular oocytes had higher caspase 3 levels (66.17 ± 11.61 vs 172.08 ± 16.95, P < 0.01) and similar GAP junction activity (5.64 ± 0.45 vs 6.29 ± 0.29). ZAR1 relative mRNA amount was lower in granular oocytes (178.27 ± 151.63 vs 0.89 ± 0.89, P = 0.01) and no effect was detected for MATER, PPP2R1A, ENY2, IGF2R, and BMP15 genes. Despite molecular differences, no detrimental effect was detected on oocyte competence in GC oocytes. Cleavage (Experiment 1: 59.52 ± 7.21% vs 59.79 ± 6.10% and Experiment 2: 68.88 ± 4.82 vs 74.41 ± 5.89%) and blastocyst (Experiment 1: 29.28 ± 4.14% vs 23.15 ± 2.96% and Experiment 2: 21.11 ± 3.28% vs 21.02 ± 6.08%) rates were similar between CC and GC (Experiments 1 and 2, respectively). Post-transfer embryo development revealed that pregnancy (CC: 24.27 ± 9.70% vs GC: 26.31 ± 7.23%) and calving (23.68% vs 33.33%) rates and fetal growth were not affected by the presence of cytoplasmic granules. Our results demonstrated that oocytes with granular cytoplasm present equivalent efficiency for IVF and calf production compared with homogenous cytoplasm oocytes. This could be observed through similar cleavage, blastocyst rates, and fetal growth development. In addition to differences in oocyte gene expression related to oocyte quality, it seems not to affect oocyte developmental competence.